2021
DOI: 10.1002/jnr.24950
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia in mice activates discrete populations of neurons throughout the brain

Abstract: The brain undergoes rapid, dramatic, and reversible transitioning between states of wakefulness and unconsciousness during natural sleep and in pathological conditions such as hypoxia, hypotension, and concussion. Transitioning can also be induced pharmacologically using general anesthetic agents. The effect is selective. Mobility, sensory perception, memory formation, and awareness are lost while numerous housekeeping functions persist. How is selective transitioning accomplished? Classically a handful of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The SON has recently been identified as a neuroendocrine substrate essential to mediate the effects of diverse general anaesthetics and sleep [6]. We explored phosphoproteome changes in the SON in response to isoflurane treatment and compared the findings in the SON with those obtained in the CC, a brain region that does not respond to anaesthesia by increasing Fos [7], and the PP, an essential part of the hypothalamo-neurohypophysial system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SON has recently been identified as a neuroendocrine substrate essential to mediate the effects of diverse general anaesthetics and sleep [6]. We explored phosphoproteome changes in the SON in response to isoflurane treatment and compared the findings in the SON with those obtained in the CC, a brain region that does not respond to anaesthesia by increasing Fos [7], and the PP, an essential part of the hypothalamo-neurohypophysial system.…”
Section: Discussionmentioning
confidence: 99%
“…These include the preoptic area, which is considered a sleep-promoting area, and the basal forebrain, lateral hypothalamic area, ventral tegmental area, and locus coeruleus those are brain regions involved in mediating sleep-arousal and anaesthesia-arousal transitions [1]. Remarkably, recent studies have identified an ensemble of neuroendocrine cells in the supraoptic nucleus (SON) of the hypothalamus persistently activated by GA [6, 7]. In elegant studies, Jiang-Xie et al [6] demonstrated that GA diminishes the expression of the immediate early gene Fos , commonly used as a marker for activated neurones, throughout the entire brain except for a subset of neurones in the SON that were persistently and commonly activated by several types of general anaesthetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After physiological monitoring, the animals were decapitated using a guillotine (OpenScience, Moscow, Russia), as described previously (Aleshin, Graf, et al, 2021). This method of euthanasia was chosen as the most suitable for our studies on the brains of adult animals in view of strong interactions of anesthetics with the metabolic changes underlying the state of wakefulness, such as neurotransmitter levels, and with action of neuroprotectants (Leary et al, 2020; Müller et al, 2011; Yatziv et al, 2021). The method followed existing recommendations (Leary et al, 2020) and was approved by the Bioethics Committee of Lomonosov Moscow State University.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the above-mentioned study analyzed LFP activity in the absence of anesthetics. , This issue is pertinent for neurotoxicology since anesthetics and analgesics can confound interpretations of electrophysiological recordings in anesthetized animals. Specifically, there is a ubiquitous presence of neurons whose activity increases during anesthesia throughout the brain . The balance in recruitment of anesthesia-on versus wake-on neuronal populations throughout the brain may be a key driver of regional and global vigilance states.…”
Section: In Situ Electroencephalographic Analysis With Measmentioning
confidence: 99%